Morphological and histopathological alterations caused by meloxicam in chick fetuses - Mervat AbdRabou; Aljohara Al- Otaibi (Bangladesh Pharmacological Society, 2022)
During pregnancy, the administration of certain drugs can cause harm to the unborn child. The purpose of the present study was to investigate the impact of meloxicam on morphological and histopathological changes in chick embryo. Forty-eight eggs were divided into four groups. After 12 days of incubation (37.8ºC, humidity - 65%), the groups were given meloxicam at varying doses. Fetuses were then removed after 48 hours. The results show that administration of high doses of meloxicam produced weakly or absence of vitelline vascularization. Also, meloxicam application instigated fetal deformities such as growth retardation, subcutaneous hemorrhage, very thin skin and exencephaly. Many histopathological alternations were noted in the retina, liver and kidney tissues of chick fetus of treated groups with meloxicam compared to the control group. The high doses of meloxicam caused many morphological and histopathological changes in the chick fetus. The safety of meloxicam was not established in this study.